Species diversity, phylogeny and evidence of recombination in begomoviruses associated with yellow mosaic disease of moth bean (Vigna aconitifolia) in South India. Issue 5 (6th February 2022) - Akram, Mohd; Kamaal, Naimuddin; Pratap, Aditya; Muin, Abdul; Agnihotri, Aniruddha Kumar; Rathore, Utkarsh Singh; Rathore, Meenal; Singh, Narendra Pratap
Abstract: Polymerase chain reaction assays of eight yellow mosaic disease (YMD) affected moth bean samples using specific primers indicated the presence of Mungbean yellow mosaic virus (MYMV), Mungbean yellow mosaic India virus (MYMIV) and Horsegram yellow mosaic virus (HgYMV) in two samples (Mo1 and Mo5) and two of these three viruses in remaining six samples. Sequence data analysis of Mo1 and Mo2 revealed the involvement of multiple DNA‐A and DNA‐B molecules in both samples. Further analysis of DNA‐A and DNA‐B molecules confirmed the presence of three viruses viz., MYMIV, MYMV and HgYMV, in Mo1 and of two MYMV and HgYMV in Mo2 samples. Analysis of common region (CR) sequences of components (DNA‐A and DNA‐B) of each virus indicated >85% nucleotide identity confirming them to be cognate and species integrity. The recombination analysis revealed the presence of a total of six putative recombination events in the viruses under study. In a phylogenetic analysis of DNA‐A sequences of the viruses under study with bipartite legume‐infecting begomoviruses and some selected old and new world begomoviruses, MYMIV, MYMV and HgYMV grouped with respective virus species. Similar grouping and clustering were found in the DNA‐B sequences also. The present study reports infection by HgYMV in moth bean and the association of three viruses (MYMIV, MYMV and HgYMV) with moth bean yellow mosaic disease for the first time. The presence of mixed infection of begomoviruses provides opportunities for the exchange of DNA between the species which may lead to the development of new strain/virus species.